The Importance of User Research Methods in User Experience Design - Chomiak-Orsa, Iwona; Łuczak, Kamila (Znaczenie badań z użytkownikami w projektowaniu User Experience, 2022)
Any aspect related to the user’s feelings when using or imagining the use of the product is referred to as User Experience (UX). The task of today’s organizations is to model the user experience in such a way that when interacting with the product, the user feels only positive emotions. However, User Experience design also requires testing the created solutions, which often turns out to be a barrier for enterprises due to the high cost of research. The purpose of this article is to present the importance of user research methods in User Experience design. The article will present the subject of UX design as a direction of application development, research methods with users in UX design and the essence of research in User Experience modeling. In order to achieve the set goal, the article uses an analysis of literature and Internet sources. After the completed analyses, it can be concluded that research with users generates added value for User Experience design on the part of both users and employees.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 1 (63), s. 1-8
Keywords: user experience; interaction design; research methods; user; requirement; projektowanie interakcji; metody badawcze; użytkownik; wymagania